2023
DOI: 10.3390/app13085196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Excavation of a Hydraulic Tunnel on Groundwater at the Wuyue Pumped Storage Power Station

Abstract: The tailwater tunnel of the Wuyue pumped storage power station is located in bedrock and extends to depths between tens and hundreds of meters. It is impossible to analyze and evaluate the whole engineering area from geological exploration data, and the hydrogeological conditions are complicated. In the early stages of the tailwater tunnel’s construction, the drinking water wells in four villages dried up. This paper reports the results from a field investigation, in situ tests, laboratory tests, and numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Additionally, Zhao et al [5] conducted some capillary rise tests on soil columns containing three layers of sandy soils with coarser over finer over coarser sandy soil to investigate the effect of the relatively finer soil interlayer. Jiang et al [6] reported the results from a field investigation to determine the influence of groundwater in the process of tunnel excavation and established a hydrogeological model of the region from the inverted regional natural flow field parameters. Meanwhile, Wang et al [7] used a numerical simulation method to establish a model of multi-seam goafs with different spacing conditions to investigate the subsidence reduction effects of various grouting schemes.…”
Section: Special Issue On the Geo-environmental Problems Caused By Un...mentioning
confidence: 99%
“…Additionally, Zhao et al [5] conducted some capillary rise tests on soil columns containing three layers of sandy soils with coarser over finer over coarser sandy soil to investigate the effect of the relatively finer soil interlayer. Jiang et al [6] reported the results from a field investigation to determine the influence of groundwater in the process of tunnel excavation and established a hydrogeological model of the region from the inverted regional natural flow field parameters. Meanwhile, Wang et al [7] used a numerical simulation method to establish a model of multi-seam goafs with different spacing conditions to investigate the subsidence reduction effects of various grouting schemes.…”
Section: Special Issue On the Geo-environmental Problems Caused By Un...mentioning
confidence: 99%